THE EVOLUTION OF MODES AND REGULATORY LOOPHOLES IN ILLEGAL INVESTMENT IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW FOLLOWING THE ESTABLISHMENT OF THE INVESTMENT VIGILANCE TASK FORCE 2.0 - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This study systematically examines the evolution of illegal investment schemes and regulatory loopholes in Indonesia following the establishment of the Investment Vigilance Task Force 2.0, using a systematic literature review (SLR) approach. The findings indicate that illegal investment schemes have shifted from conventional schemes to complex digital forms, ranging from money games, trading bots, fake crypto investments, to social media-based platforms and communication groups. On the other hand, regulations still contain serious loopholes, such as fragmentation of authority among agencies, policy delays in response to technological innovation, weak coordination of law enforcement, and limitations in cross-jurisdictional regulation. This study concludes that a holistic approach is needed, integrating cross-sectoral regulatory strengthening, the utilisation of technology-based regulation, and the improvement of public financial literacy to break the chain of evolution of illegal investment schemes in the SWI 2.0 era.